A Comparison of Anthropometric, Metabolic, and Reproductive Characteristics of Young Adult Women from Opposite-Sex and Same-Sex Twin Pairs - Korsoff, Pirkko; Bogl, Leonie; Korhonen, Päivi; Kangas, Antti J.; Soininen, Pasi; Ala-Korpela, Mika; Rose, Richard J.; Kaaja, Risto; Kaprio, Jaakko (Frontiers in Endocrinology, 2014)
Background: Prenatal exposure to androgens has been linked to masculinization of several traits. We aimed to determine whether putative female intra-uterine exposure to androgens influences PCOS-related phenotypes, including anthropometric, metabolic and reproductive parameters using a twin design. Methods: Two cohorts of Finnish twins born in 1975-1979 and 1983-1987 formed the basis for the longitudinal FinnTwin16 (FT16) and FinnTwin12 (FT12) studies. Self-reported anthropometric characteristics, disease status and reproductive history were compared between 679 same-sex (SS) and 789 opposite-sex (OS) female twins (mean age ± SD: 34 ± 1.1) from the wave 5 of data collection in FT16. Serum lipid and lipoprotein subclass concentrations measured by nuclear magnetic resonance spectroscopy were compared in 226 SS and 169 OS female twins (mean age ± SD: 24 ± 2.1) from wave 4 of data collection in FT12 and FT16. Results: Anthropometric measures, the prevalence of hypertension and diabetes mellitus type 2 did not differ significantly between females from SS and OS twin pairs at age 34. Similarly, the prevalence of infertility, age at first pregnancy and number of induced and spontaneous abortions did not differ significantly between these two groups of women. The serum lipid and lipoprotein profile did not differ between females from SS and OS twins at age 24. Conclusion: We found no evidence that androgen overexposure of the female fetus affects obesity, metabolic profile or reproductive health in young adult females. However, these results do not exclude the possibility that prenatal androgen exposure in females could be adversely associated with intermediate phenotypes of PCOS later in life.